Penegakan Hukum terhadap Pelanggaran HAM di Pulau Rempang - Anisa Tri Ariyani; Dodi Jaya Wardana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the social and economic impacts of the Rempang Eco City development project on Rempang Island, Batam City, which involves theiBatam Business Agency and the private company PT Makmur Elok Graha. The background to the problem involves a conflict between local residents and joint forces that occurred on September 7 2023, in connection with a land dispute and the relocation of residents. The research objective is to analyze this conflict in a social, economic and human rights context, and identify its implications for local communities. Another of purpose is to examine the human rights enforcement in Indonesian legal and political system. The research methodology includes field data collection through observations and interviews, as well as analysis of project-related documents. The research conclusion is that this conflict must be seen as a serious problem involving various dimensions, and its resolution requires attention to human rights, community participation.